Безопасность жизнедеятельности. Лабораторный практикум: учебное пособие - Амелькович Ю. А. Юлия Александровна; Анищенко Ю. В. Юлия Владимировна; Вторушина А. Н. Анна Николаевна; Гуляев М. В. Милий Всеволодович; Гусельников М. Э. Михаил Эдуардович; Дашковский А. Г. Анатолий Григорьевич; Задорожная Т. А. Татьяна Анатольевна; Извеков В. Н. Владимир Николаевич; Кагиров А. Г. Артур Геннадьевич; Костырев К. М. Константин Михайлович; Панин В. Ф. Владимир Филиппович; Плахов А. М. Александр Митрофанович; et al. (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана